The Glance of the Liberal Reforming Policy on the Territories of the Argentine South, 1898-1916 (Quinto Sol, 2010)
Around 1900, the Argentine opinions agreed in the idea that the nationalization of the National Territories recently formed had failed. This circumstance agrees with the sprouting of a reformist current within the liberal oligarchy, and also of an abundant production in the field of the social thought. We analyzed the most important discourse of that trend in relation to the Territories of the South, mainly Estanislao Zeballos and Joaquín V. González writings. Their ideas about the progress of those spaces and their joint with the nation proposed a status of internal colonies and delayed the construction of political citizenship.
Keywords: Liberal reformists; National Territories; Zeballos; González